SURVEI PEMBINAAN OLAHRAGA TENIS USIA DINI SEKOLAH TENIS NEW ARMADA KABUPATEN MAGELANG (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2013)
The research aims to determining the implementation of tennis coaching to young children at New ArmadaSchool Tennis, Magelang regency. This research conducted a descriptive qualitative approach. The researchsubjects include administrators, coaches, athletes and athletes’ parents. The writer took the data by usinginterviews, observation,and documentation. Data analysis was done by data collection, review of the data, datareduction, data presentation and data verifications. Then the results showed that: (1) coaching that was donewere promoting and young children development has been running well, but the talent scouting has not beenimplemented, (2) training program implemented was in the poor category, due to the weakness of plannedtraining program for daily exercise and match preparation training, (3) the condition of the facilities andinfrastructure has been standard and adequate, (4) management of the organization was in unfavorablecategory because of the elements of the organization have not been well-implemented, (5) the coach has alreadyhad a national certificate and has planned exercise program that is adjusted to each class athletes (6) theachievements of athletes New Armada Tennis School still unsatisfactory to the national level. Therefore, it canbe Concluded from this research that the implementation of young children sports coaching at New ArmadaTennis Schools has not been going well.